Lexicalization Patterns of English and Armenian Verbs of “Speech Activity” - Badalyan, Lilit (Armenian Folia Anglistika, 2012)
The article studies the relation between the lexicalization patters of English and Armenian verbs of speech activity and their syntactic characteristics based on L. Talmy’s typology. The latter distinguishes between two types of languages – the so-called “satellite-framed” languages where the semantic component of manner of the action is lexicalized in the meaning of motion verbs, and the direction of the action is expressed by other means and “verb-framed” languages where the meaning of the verb comprises the component of the direction of the action. An attempt has been made to apply Talmy’s theory to a semantic group of English and Armenian verbs of speech activity choosing 80 English and 60 Armenian verbs which contain the semantic component of the manner of action. For a clearer picture 2000 sentences from the National British Corpus and 1500 sentences from Eastern Armenian corpus have been studied since the syntactic possibilities of verbs are largely conditioned by various combinations of the semantic components of the meaning of verbs.